2019
DOI: 10.1186/s13287-019-1479-3
|View full text |Cite
|
Sign up to set email alerts
|

A magic kick for regeneration: role of mesenchymal stromal cell secretome in spermatogonial stem cell niche recovery

Abstract: BackgroundInjury of stem cell niches may disturb tissue homeostasis and regeneration coordinated by specific niche components. Yet, the mechanisms of stem cell niche restoration remain poorly understood. Herein, we examined the role of mesenchymal stromal cells (MSCs) as pivotal regulators of stem cell niche recovery focusing on the effects of their secretome.MethodsThe spermatogonial stem cell (SSC) niche was selected as a model. SSC niches were injured by inducing abdominal cryptorchidism in rats. Briefly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 40 publications
(33 reference statements)
0
24
0
3
Order By: Relevance
“…Therefore, injecting the MSC secretome can help attract lost Sertoli cells from the pools of progenitor cells. This assumption was indirectly supported by the restoration of the Sertoli cell pool without visible proliferation at the observed control points in vivo, as well as the stimulation of Sertoli cell migration by MSC secretion in vitro (Figueiredo et al, 2016;Sagaradze et al, 2019a).…”
Section: Mscs Regulate Tissue Regeneration By Restoring the Cellular mentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, injecting the MSC secretome can help attract lost Sertoli cells from the pools of progenitor cells. This assumption was indirectly supported by the restoration of the Sertoli cell pool without visible proliferation at the observed control points in vivo, as well as the stimulation of Sertoli cell migration by MSC secretion in vitro (Figueiredo et al, 2016;Sagaradze et al, 2019a).…”
Section: Mscs Regulate Tissue Regeneration By Restoring the Cellular mentioning
confidence: 89%
“…In tissue-specific stem cell niches, MSCs might provide regulatory factors restricting the injury-induced responses of niche cells. Hence, we suppose that the ability of MSCs to restore the SSC niche due to the effects of their secretome, which we observed in a rat model of abdominal cryptorchidism (Sagaradze et al, 2019a ), could be at least partially mediated by secreted insulin-like growth factor-binding proteins (IGFBPs) (Kalinina et al, 2015a ). Niche damage causes hyperplasia of the interstitial compartment where Leydig cells localize and produce insulin-like growth factor 1 (IGF1) that is critical for the functioning of both SSCs and supporting cells.…”
Section: Mechanisms Of Msc Participation In Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, intratesticular administration of stromal MSCs or MSC secretomes was sufficient to improve production of germ cells in experimentally induced cryptorchidism in rats [Sagaradze et al, 2019]. Also, two studies Dessouky/Gouda/Arafa/Elewa/Abo-Ouf/ Askar Cells Tissues Organs 2020;209:83-100 98 DOI: 10.1159/000510363 have shown that murine bone marrow MSCs can differentiate into testicular germ cells in immature rats [Nayernia et al, 2006] and in a mouse model of busulfaninduced infertility [Lue et al, 2007], while another two studies reported differentiation of transplanted bone marrow MSCs into Leydig cells [Yazawa et al, 2006;Xing et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, they possess an ability to proliferate and differentiate into a variety of tissue-specific cells, and on the other, they produce tissue-specific matrix and release soluble factors that orchestrate tissue renewal and repair (14,15). Deep involvement in tissue homeostasis maintenance makes these cells a lucrative object for study and potential application in regenerative medicine (16,17). Nevertheless, we still have much to find out about the factors and molecular machinery that regulates the functions of these cells (18).…”
Section: Introductionmentioning
confidence: 99%